2017
DOI: 10.1007/s12088-017-0677-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Cloned Bacillus subtilis Keratinase and Its Insinuation in Psoriasis Treatment Using Docking Studies

Abstract: Present study demonstrated the expression of cloned RSE163 keratinase gene and in silico binding affinities of deduced protein with psoriasis topical drugs for systemic absorption and permeation through skin. The gene expressed in showed significantly higher keratinase activity 450 ± 10.43 U representing 1342 bp nucleotides encoding 447 amino acids with molecular weight of 46 kDa. The modeled structure was validated using ramachandran's plot showing 305 residues (84.3%) in most favoured region. Docking studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The quality factor of the predicted model was observed as 83.09 using ERRAT2. Gupta et al [63] validated the modeled structure of the B. subtilis RSE163 keratinase gene using Ramachandran's plot and results showed that 305 of the amino acid residues (84.3%) were in the favored region. Compared with the previous study by Gupta et al [63], the current model is relatively better as 91.98% of the amino acid residue is in the most favored region.…”
Section: Structure Modeling and Analysis Of Wild-type Keratinase And Mutantsmentioning
confidence: 99%
“…The quality factor of the predicted model was observed as 83.09 using ERRAT2. Gupta et al [63] validated the modeled structure of the B. subtilis RSE163 keratinase gene using Ramachandran's plot and results showed that 305 of the amino acid residues (84.3%) were in the favored region. Compared with the previous study by Gupta et al [63], the current model is relatively better as 91.98% of the amino acid residue is in the most favored region.…”
Section: Structure Modeling and Analysis Of Wild-type Keratinase And Mutantsmentioning
confidence: 99%
“…Keratinases are serine and metalloproteases, and their active sites are formed by several conserved residues. Crystal structures of several keratinases demonstrate the structural basis for their activity and provide insights into designing more stable and efficient enzymes for industrial applications ( Betzel et al, 2001 ; Gupta et al, 2017 ). These structures can also be utilized as a template to obtain homology models of other keratinases ( Kluskens et al, 2002 ).…”
Section: Mechanism Of Action For Keratinasementioning
confidence: 99%
“…They are also added to cosmetic formulas for skin care, with whitening, freckle-removal (Yang et al, 2012), anti-wrinkle, and anti-skin aging effects (Yeo et al, 2018). Studies have demonstrated the remarkable curative effects of keratinases in the treatment of hyperkeratosis, such as in corns, calluses, and psoriasis (Gupta et al, 2017). Similarly, keratinases are effective in treating acne and pimples, common skin problems caused by excessive keratin accumulation in sebaceous glands (Spyros et al, 2003).…”
Section: Effects On Skin and Tissuesmentioning
confidence: 99%
“…Different methods for determining keratinase activity have been developed based on the choice of different substrates. At present, the most used substrates in keratinase activity determination are azo keratin (Lin et al, 2009a;Huang et al, 2017), azure keratin (Nahar et al, 2016;Pawar et al, 2018), soluble keratin (Fang et al, 2014Su et al, 2017;Wang et al, 2019), and feather powder Gupta et al, 2017;Jin et al, 2019;Yong et al, 2020). It must be pointed out that considering the substrate differences in solubility and composition, as well as substrate preference of keratinase, the activity determined by different substrates may differ greatly.…”
Section: Determination and Definition Of Keratinase Activitymentioning
confidence: 99%